Representations and uses of indigenous areas in tourism experiences in the Russian Arctic. (3rd April 2017) - Pashkevich, Albina; Keskitalo, E. Carina H.
ABSTRACT: This paper compares the representation of indigenous tourism experiences in advertisement materials with representations gathered from site visits and tourism sector interviews in the Nenets Autonomous Okrug (NAO) in northern Russia. The study shows that a majority of the visual images and text used for marketing of the area construct a picture of an indigenous people living 'in harmony' with nature, representing a romanticized and historical image of indigenous communities. In contrast with these marketing images, large variations exist in everyday practices and among the numerous practical considerations related to the recent and limited development of tourism in the NAO.